2022
DOI: 10.1590/1983-40632022v5272755
|View full text |Cite
|
Sign up to set email alerts
|

Leaf inoculation of Azospirillum brasilense and Trichoderma harzianum in hydroponic arugula improve productive components and plant nutrition and reduce leaf nitrate

Abstract: Using beneficial fungi and bacteria to plant growth may reduce the leaf nitrate content and improve the quality of produced food. This study aimed to evaluate the isolated and combined effect of inoculation with Azospirillum brasilense and Trichoderma hazianum at two electrical conductivities on the nutrition and production of hydroponic arugula cultivation. The experiment was designed in randomized blocks, in a 4 x 2 factorial scheme, with five replications. The treatments consisted of inoculations (non-inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Furthermore, seeds treated with Trichoderma were found to have improved growth and physiological performance in a hydroponic saline environment, as evidenced by constantly faster and more uniform seed germination compared to untreated seeds ( Yasmeen and Siddiqui, 2018 ). Practices in hydroponic systems showed that inoculation with Trichoderma provided higher fresh leaf yields, resulting in a 15%-18% reduction in fertilizer use ( Moreira et al., 2022 ; Oliveira et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, seeds treated with Trichoderma were found to have improved growth and physiological performance in a hydroponic saline environment, as evidenced by constantly faster and more uniform seed germination compared to untreated seeds ( Yasmeen and Siddiqui, 2018 ). Practices in hydroponic systems showed that inoculation with Trichoderma provided higher fresh leaf yields, resulting in a 15%-18% reduction in fertilizer use ( Moreira et al., 2022 ; Oliveira et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For other species of fruit-producing vegetables, such as tomatoes, it was also found that exposure of plants to A. brasilense resulted in greater photosynthetic capacity, in addition to significant growth of the shoot and roots of the plants, when compared to the control treatment, which is closely related to the Bars with the same lowercase letter do not differ from each other by the Tukey test (p ≤ 0.05); AZF -2 mL L -1 of A. brasilense applied via foliar spray; AZFN -300 mg L -1 of nicotinamide combined with 2 mL L -1 of A. brasilense applied via foliar spray; AZS -2 mL L -1 of A. brasilense applied to the hydroponic solution; AZSN -300 mg L -1 of nicotinamide applied via foliar spray combined to 2 mL L -1 of A. brasilense applied to the hydroponic solution greater production of proteins mainly involved in the processes of photosynthesis, respiration, and organization of chloroplasts (Lade et al, 2018). In addition, for lettuce and arugula crops, under hydroponic system conditions, this bacteria significantly increased leaf nutrient content, boosting plant growth and root development (Oliveira et al, 2022;2023).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of the use of new inputs, the use of biostimulants has stood out in the cultivation of grainproducing species, such as corn (Colla et al, 2021), but has also gained prominence for application in the cultivation of horticultural species (Garcia et al, 2023;Gaiotto et al, 2023). Thereby, one of the products that stand out is made up by Azospirillum brasilense, which promotes plant growth, improves photosynthetic efficiency, and increases hormonal, nutritional, and pigment content, also modulating the expression of genes that promote growth, yield, and quality of vegetables, including under hydroponic cultivation Oliveira et al, 2022;2023).…”
Section: Introductionmentioning
confidence: 99%
“…BPCPs e FPCPs são capazes de produzir e liberar fitohormônios, contribuindo para o crescimento radicular, aumentando a absorção de nutrientes, melhorando a tolerância ao estresse e promovendo um crescimento vegetal vigoroso e equilibrado. Dentre os fitohormônios, destacamos o grupo das auxinas, citocininas e giberelinas (OLIVEIRA et al, 2022).…”
Section: Produção De Fitohormôniosunclassified
“…O Trichoderma atua como um agente de controle biológico, suprimindo patógenos e estimulando o crescimento radicular das plantas. Por sua vez, o Azospirillum, bactéria promotora de crescimento, promove a FBN e a produção de fitohormônios, resultando em um aumento significativo do crescimento e desenvolvimento das plantas (OLIVEIRA et al, 2022).…”
Section: Coinoculaçãoa Associação Do Trichoderma Com Azospirillum Pot...unclassified